Adipocyte-derived extracellular vesicles promote breast cancer cell malignancy through HIF-1α activity. (28th November 2021) - La Camera, Giusi; Gelsomino, Luca; Malivindi, Rocco; Barone, Ines; Panza, Salvatore; De Rose, Daniela; Giordano, Francesca; D'Esposito, Vittoria; Formisano, Pietro; Bonofiglio, Daniela; Andò, Sebastiano; Giordano, Cinzia; et al.
Abstract: Extracellular vesicles (EVs) are emerging key protagonists in intercellular communication between adipocytes and breast cancer (BC) cells. Here, we described a new mechanism by which EVs released by mature adipocytes promoted breast cancer cell malignancy "in vitro" and "in vivo". We found that adipocyte-derived EVs enhanced growth, motility and invasion, stem cell-like properties, as well as specific traits of epithelial-to-mesenchymal transition in both estrogen receptor positive and triple negative BC cells. Of note, adipocyte-derived EVs aid breast tumor cells in lung metastatic colonization after tail-vein injection in mice. These EV-mediated effects occur via the induction of HIF-1α activity, since they were abrogated by the use of the HIF-1α inhibitor KC7F2 or in cells silenced for HIF-1α expression. Moreover, using an "ex vivo" model of obese adipocytes we found that the depletion of EVs counteracted the ability of obese adipocytes to sustain pro-invasive phenotype in BC cells. Interestingly, EVs released by undifferentiated adipocytes failed to induce aggressiveness and HIF-1α expression. These findings shed new light on the role of adipocyte-derived EVs in breast cancer progression, suggesting the possibility to target HIF-1α activity to block the harmful adipocyte-tumor cell dialogue, especially in obese settings. Highlights: Adipocyte-derived extracellular vesicles promote breast cancer metastatic phenotype. HIF-1α mediates adipocyte-derived extracellular vesicle effects in breast cancer. HIF-1α as a new potential therapeutic target for obese breast cancer patients.